The Optometric Care of Vision Problems After Concussion: A Clinical Guide. - D’Angelo, Miki Lyn; Tannen, Barry (Optometry & Visual Performance, 2015)
Over the past decade, there has been a surge in the diagnosis of sports-related concussions. The etiology of this increase may be the cultural emphasis placed on physical activity, the heightened awareness of the signs and symptoms of concussion leading to better, more accurate diagnosis, or a combination of these two factors. Regardless, there is increased recognition that a number of concussion patients retain persistent symptoms which do not resolve within three months, resulting in the diagnosis of Post-Concussion Syndrome. Often, many of the lingering symptoms are visual in nature, with patients having difficulty with visual attention, decreased reading speed and comprehension, headaches, asthenopia, photophobia, and difficulty processing in busy visual environments. Research over the past ten years provides evidence that post-concussion patients have accommodative, vergence, oculomotor, and visual-vestibular dysfunctions to correlate with these symptoms; research has further classified this type of traumatic brain injury as Post-Traumatic Vision Syndrome (PTVS). Awareness of this syndrome is in its infancy, and there is a paucity of clinical information to help optometrists provide care for these patients. The goal of this paper is to be a clinical guide to the identification, treatment, and management of patients with PTVS.